Removal of selected toxic elements by surface modified multi-walled carbon nanotubes from contaminated groundwater in Sekhukhune, Limpopo - Thobakgale, Ruth Dipuo (My University, 2022)
Water contamination caused by toxic elements has serious human health and ecological implications. The increasing quantity of toxic elements in surface and groundwater is currently an area of greater concern, especially since many industries are discharging their metal containing effluents into freshwater without any adequate treatment. The mineral dissolution in mining regions is highly enhanced by mining and smelting activities. The mine waste and drainage in areas surrounding mines have high levels of toxic element contamination above the permissible limits. Contamination of groundwater by toxic elements such as As, Fe, Mn, Al, Cr, Zn and Co due to operational activities of surrounding mines in the Sekhukhune district was reported by several researchers. Removal of toxic elements from contaminated water is a big challenge. The affected communities need to attain a safe water supply source for daily usage, hence there is an urgent need of technologies for the treatment of water supplies contaminated with these toxic elements to ensure the safety of potable water. The study was undertaken by modifying nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) and investigating the removal of chromium, nickel and lead from anthropogenic contaminated groundwater in the Sekhukhune area, in Limpopo. The as-prepared N-MWCNTs functionalised with metal oxide, thiol and amino functional groups are expected to increase the surface area of the nanocomposite, which can facilitate high adsorption of contaminants from water samples. The adsorption capabilities for the removal of these toxic elements by modified N MWCNTs nanocomposites were investigated in batch studies as a function of different parameters. The parameters studied included pH, contact time, adsorbent dosage, initial concentration, temperature, competing ions and reusability. The optimum condition was then acquired for removal of selected toxic elements from real water studies. The removal efficiencies of the as-prepared nanocomposites were pH dependent and the optimal pH values for adsorption was 5.5, 1.5, 11 and 6 at optimum contact time of 10, 80, 60 and 120 min and dosage of 0.30, 0.35, 0.05 and 0.6 g/L for Cr(III), Cr(VI), Ni(II) and Pb(II), respectively. The prepared nanocomposites were characterised using various techniques such as Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmet-Teller (BET) and thermogravimetric analysis (TGA). The FTIR analysis confirmed the presence of Fe3O4, -SH and -NH2 groups on the functionalised MWCNTs. The PXRD analysis further supported that the synthesized nanocomposites consisted of hexagonal graphite structure of MWCNTs. Furthermore, SEM and TEM results showed that the introduced functional groups were uniformly attached on the surface of the MWCNTs. The BET analysis indicated that the surface area of the modified MWCNTs nanocomposites increased significantly as compared to the acid treated MWCNTs. In addition, TGA showed that the M-MWCNTs (M = modified) nanocomposites possess high thermal stability. Raw N-MWCNTs showed higher stability as compared to oxidised N-MWCNTs, which decomposes at lower temperatures of 200 °C. No weight loss was observed below 800 °C for the hydrazine functionalised nanocomposites as compared to the triethylenetetramine (TETA)- substituted nanocomposites, which showed weight loss at 300 °C. Toxic elements in solutions before and after treatment were quantified using flame atomic absorption spectrometry (F-AAS). The adsorption isotherms of the as-prepared nanocomposites for chromium, nickel and lead removal fitted both the Langmuir and Freundlich model depending on the adsorbent used, which suggest that the adsorption process met both monolayer and heterogeneous adsorption. Thermodynamic analysis showed that the adsorption of Cr(III), Cr(VI), Ni(II) and Pb(II) ions are spontaneous and endothermic. The as-prepared nanocomposites showed an outstanding regeneration performance retaining over 50% toxic elements removal. Thus, the as prepared nanocomposites are promising for practical application in toxic element treatment. Analysis of the collected river and borehole water in Sekhukhune indicated that the concentration of total chromium, nickel and lead before treatment varied from (0.207 to 0.286 mg/L), (0.226 to 0.380 mg/L) and (3.301 to 8.017 mg/L), respectively which were above acceptable levels recommended by the South African National Standards (SANS), United States Environmental Protection Agency (USEPA) and World Health Organisation (WHO), i.e., 0.05 mg/L, 0.07 mg/L and 0.01 mg/L. After treatment, the nanocomposites were able to remove 100% of the metal ions from the water. TETA-functionalised nanocomposites showed greater removal efficiencies in comparison to the hydrazine-functionalised nanocomposites for all the studies done.
Thesis (M.Sc.(Chemistry)) -- University of Limpopo, 2022
Keywords: Water; Water contamination; Toxic elements; Mine waste; Nitrogen-doped multi-walled carbon nanotubes; Water -- Pollution; Water quality -- South Africa -- Limpopo; Groundwater -- South Africa -- Limpopo; Carbon nanotubes; Mineral industries -- Waste disposal